“… I denne Tid maa man ogsaa kunde taale at se Blod”. Frits Clausen i russisk krigsfangenskab 1915-18 - Lauridsen, John T. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Frits Clausen, the future leader of the Nationalist Socialist Workers Party of Denmark (DNSAP), was a Russian prison of war from 1915-18. The development that he underwent in captivity is examined through contemporary letters and later articles and reminiscences. He was forced to enlist in the German army as a professed Danish nationalist, and for him the war represented a possibility and a hope that Germany would lose, providing an opportunity for North Schleswig to be reunited with Denmark. He put this goal higher than other considerations, including the German orientation of Schleswigers, and his dislike of the Danish Social-Liberal Party was due in an inordinate degree to press releases from Denmark reporting the party’s half-hearted attitude to the North Schleswig issue. He also clashed with the Danish clergyman who was sent to minister to the prisoners of war from North Schleswig. The clergyman was more of an upright, neutral Danish official than a wholehearted advocate of the North Schleswig case. In this respect the clergyman was a disappointment in Frits Clausen’s eyes. His recommendation that the pro-Danish prisoners of war from North Schleswig should return to Germany to resuming fighting on the German side following the separate peace treaty between Germany and Russia was more than Frits Clausen could cope with. He went over the clergyman’s head and tried, together with a small number of like-minded individuals, to fight against Germany, but his attempt failed. In the course of his endeavours he developed a hatred of the new Soviet regime, as personified by the Marxist Jew, but in other respects had gained an excellent impression of the Russians, who he in no way considered to be an inferior people. On his return from Russia he expressed his anti-Semitism and anti-Communism in various anonymous articles in the press. This was the first step towards keeping the promise, made to himself during his captivity, to dedicate his life to the struggle against Marxism.